READING AS AN IMPORTANT SOURCE OF VOCABULARY REPLENISHMENT FOR STUDENTS - Sagidullayeva Shakhnoza Baxitjanovna (Western European Studies, 2025)
This article provided information about the pedagogical importance, conditions, methods, means of improving the vocabulary of students. The reading approach is scientifically based on the fact that readers are an important means of increasing vocabulary. The pedagogical possibilities of Group and individual organization of reading activities in increasing the vocabulary of students have been analyzed.
Keywords: Reader; vocabulary; reading; educational process